The role of polyamines in gastric mucus synthesis inhibited by cigarette smoke or its extract. (1st August 2000) - Ma, L; Wang, W P; Chow, J Y C; Lam, S K; Cho, C H
Abstract : BACKGROUND: Cigarette smoking was shown to delay gastric ulcer healing and reduce synthesis of mucus, which is important for gastric ulcer protection and healing. Polyamines are important in these processes. AIMS: To study the effects of cigarette smoking on the synthesis of mucus and to investigate if such an effect is acting by interference with the polyamine pathway. METHODS: Gastric mucosal ornithine decarboxylase activity, mucous secreting layer thickness, and ulcer size were determined after different concentrations of cigarette smoke exposure (0, 2, or 4%) in intact animals and animals with ulcers. Synthesis of mucus and ornithine decarboxylase activity and mRNA expression were also assessed in cigarette smoke extract treated MKN-28 cells. RESULTS: Exposure to cigarette smoke significantly reduced the thickness of the mucous secreting layer and gastric mucosal ornithine decarboxylase activity in animals with or without ulcers. Spermidine not only reversed inhibition of mucus synthesis in both intact and ulcer bearing animals but also reversed the delay in ulcer healing. Cigarette smoke extract significantly reduced mucus synthesis and ornithine decarboxylase activity but not its mRNA expression in MKN-28 cells. The reduction in mucus synthesis was restored by spermidine. CONCLUSIONS: Cigarette smoke and its extract repress mucus synthesis in vivo and in vitro, respectively. Reduction of ornithine decarboxylase activity in gastric mucosa is closely associated with this effect.